IMPLEMENTASI STRATEGI INDEX CARD MATCH UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Farida Isroini; Ulva Badi’ Rahmawati; Fahmi Khumaini; Ida Fauziatun Nisa' (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
Active learning is an important factor in the success of the learning process. The Index Card Match strategy is one of the learning strategies that can make learning more interesting and active, so that it can be applied to all students and foster new ideas and creativity on how to create a much better and more enabling environment for students and support they are in the learning process. The background of this research is that the learning process of students is still less active, whose learning process uses the lecture method or direct learning centered on educators. Therefore, it causes the learning process to be less interesting and the creativity of students is still low and has an impact on the activity of students during the learning process. The approach used for this research is a qualitative approach in the form of descriptive research. This type of thesis research includes field research, which is to describe and describe the situation and phenomena more clearly regarding the situation that occurred. Data analysis can be done through data reduction, data presentation, and drawing conclusions.